Efficacy and safety of Chinese herbal medicine for depression: A systematic review and meta-analysis of randomized controlled trials. (October 2019) - Wang, Yong; Shi, Yi-hua; Xu, Zhen; Fu, Huan; Zeng, Hua; Zheng, Guo-qing
Abstract: Objective: To conduct a systematic review to assess the current evidence available for the effectiveness and safety of Chinese herbal medicine (CHM) for depression. Methods: An electronic search was conducted in eight databases from inception until April 2018. Randomized controlled trials with risk of bias (RoB) score ≥ 4 according to the Cochrane RoB tool were included for analyses. The primary outcome was the severity of depression. The secondary outcomes were total effective rate (TER) and adverse events. The minimally important difference (MID) of the severity of depression was a reduction in the Hamilton Rating Scale for Depression 17 items (HAMD-17) scores by 4. RevMan 5.3 Software was used for data analyses. GRADE system was used to assess the certainty of evidence. Results: A total of 40 eligible studies with 3549 subjects were identified. Meta-analyses showed that CHM monotherapy had better clinically effects than placebo according to HAMD-17 score (Mean Difference (MD) = −4.53, 95% CI (−5.69, −3.37), P < 0.00001; Certainty of evidence: Moderate) and TER (Risk Ratio (RR) = 2.15, 95% CI (1.61, 2.88), P < 0.00001, Certainty of evidence: Low). Meta-analyses showed that CHM was as effective as western conventional medications (WCM) in TER (RR = 0.99, 95% CI (0.95, 1.02), P = 0.41, Certainty of evidence: High) and in reducing HAMD-17 score (MD = 0.44, 95% CI (−0.11, 0.99), P = 0.12, Certainty of evidence: Moderate). Meta-analyses showed that CHM in combination with WCM was better than WCM in TER (RR = 1.16, 95% CI (1.07, 1.27), P = 0.0004, Certainty of evidence: High), while had comparable clinically effects with WCM according to HAMD-17 score (MD = −2.51, 95% CI (−3.24, −1.77), P < 0.00001, Certainty of evidence: Moderate). In additional, CHM were associated with less adverse events than WCM, and adding CHM to WCM reduced adverse events. Conclusion: The findings of present systematic review, at least to a certain extent, provided supporting evidence for the routine use of CHM for depression.